Short-Chain Fatty Acid and FFAR2 Activation – A New Option for Treating Infections? - Schlatterer, Katja; Peschel, Andreas; Kretschmer, Dorothee (Frontiers in Cellular and Infection Microbiology, 2021)
The human innate immune system is equipped with multiple mechanisms to detect microbe-associated-molecular-patterns (MAMPs) to fight bacterial infections. The metabolite short-chain- fatty-acids (SCFAs) acetate, propionate and butyrate are released by multiple bacteria or are food ingredients. SCFA production, especially acetate production, is usually essential for bacteria, and knockout of pathways involved in acetate production strongly impairs bacterial fitness. Because host organisms use SCFAs as MAMPs and alter immune reactions in response to SCFAs, interventions that modulate SCFA levels can be a new strategy for infection control. The interaction between SCFAs and host cells has been primarily investigated in the intestinal lumen because of the high local levels of SCFAs released by bacterial microbiome members. However, members of not only the intestinal microbiome but also the skin microbiome produce SCFAs, which are known ligands of the seven-transmembrane G-protein-coupled-receptor FFAR2. In addition to enterocytes, FFAR2 is expressed on other human cell types, including leukocytes, especially neutrophils. This finding is in line with other research that determined that targeted activation of FFAR2 diminishes susceptibility toward various types of infection by bacteria such as Klebsiella pneumonia, Citrobacter rodentium, and Staphylococcus aureus but also by viruses such as respiratory syncytial and influenza viruses. Thus, our immune system appears to be able to use FFAR2-dependent detection of SCFAs for perceiving and even averting severe infections. We summarize recent advances in understanding the role of SCFAs and FFAR2 in various infection types and propose the manipulation of this receptor as an additional therapeutic strategy to fight infections.